A randomized controlled trial to test the effectiveness of thymus honey on xerostomia in head and neck cancer patients undergoing radiotherapy - Charalambous, M.; Katodritis, N.; Vomvas, D.; Raftopoulos, Vasilios; Georgiou, M.; Lambrinou, Ekaterini; Pitsillides, V.; Charalambous, Andreas (My University, 2015)
Introduction: Previous studies have shown that xerostomia is the most frequent complication among patients who receive radiotherapy. The prevalence of xerostomia has been reported to be from 73.5% to 93%. Despite the use of techniques such as sparing the parotid glands and intensity-modulated radiotherapy, xerostomia continues to be cited by patients as a major cause of decreased quality of life (QoL).
Keywords: Xerostomia; Thymus honey